2022
DOI: 10.33476/jobs.v3i1.2472
|View full text |Cite
|
Sign up to set email alerts
|

Peran Inovasi, Kolaborasi dan Media Sosial terhadap Kinerja Usaha UMKM di DKI Jakarta

Abstract: Merujuk pada teori Resource Based View, tujuan penelitian ini adalah untuk mengetahui kinerja usaha pada UKM di wilayah DKI Jakarta yang mengalami penurunan penjualan. Penelitian ini  dianalisa dengan metode regresi linier berganda. Sampel yang dugunakan adalah UKM binaan Dinas PPAPP DKI Jakarta sebanyak 72 responden dengan non probability sampling metode purposive sampling. Hasil yang diperoleh menunjukkan bahwa dari tiga variabel yang diangkat, yaitu inovasi, kolaborasi dan media sosial, variabel inovasi sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Research conducted by [25] has demonstrated that collaboration yields advantageous and noteworthy impacts on corporate performance. Similarly, [34] did research that is consistent with [35], [29], [36]. In other words, collaboration in a business context is the best mechanism for inter-organizational cooperation, if the organization wants to achieve its goals.…”
Section: Collaboration Relationship With Business Performancementioning
confidence: 69%
See 1 more Smart Citation
“…Research conducted by [25] has demonstrated that collaboration yields advantageous and noteworthy impacts on corporate performance. Similarly, [34] did research that is consistent with [35], [29], [36]. In other words, collaboration in a business context is the best mechanism for inter-organizational cooperation, if the organization wants to achieve its goals.…”
Section: Collaboration Relationship With Business Performancementioning
confidence: 69%
“…Company performance is a representation of the company's overall state during a specific time period, which is a result or achievement impacted by the company's operational actions in utilizing its resources [28]. According to [29], business performance indicators are 1) Sales growth rate, 2) Capital growth rate, 3) High workforce growth rate, 4) Extensive market growth rate, and 5) Profit growth rate.…”
Section: Business Performancementioning
confidence: 99%
“…Inovasi memiliki hubungan positif yang kuat pada kinerja bisnis (Chen, 2019) . Hal ini mempengaruhi bisnis coffee shop di Kabupaten Aceh Barat karena para pemilik coffee shop harus terus mengikuti tren inovasi terbaru untuk tetap bersaing di pasar (Deviastri & Annisa, 2022). Dengan inovasi yang tepat, bisnis coffee shop di Kabupaten Aceh Barat dapat terus berkembang dan memenuhi kebutuhan pasar yang semakin beragam.…”
Section: Pendahuluanunclassified